2021
DOI: 10.3390/ejihpe11010016
|View full text |Cite
|
Sign up to set email alerts
|

Immune Fitness and the Psychosocial and Health Consequences of the COVID-19 Pandemic Lockdown in The Netherlands: Methodology and Design of the CLOFIT Study

Abstract: This article provides an overview of the design and methodology of the “Corona lockdown: how fit are you?” (CLOFIT) study, including the questionnaires and scales that were included in the online survey. The aim of the CLOFIT study was to investigate the psychosocial and health consequences of the coronavirus disease 2019 (COVID-19) pandemic in the Netherlands. The survey was conducted among the Dutch population to collect data on immune fitness and the psychological and health consequences of the 2019 coronav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 67 publications
1
28
0
Order By: Relevance
“…In contrast, a reduction in alcohol consumption was shown to be an adequate coping mechanism for lockdown related mood and stress effects, for maintaining adequate immune fitness, and to reduce their susceptibility of experiencing COVID-19-related symptoms. Our findings, summarized in Figure 7, are in line with previous publications outlined in the introduction, showing that the COVID-19 lockdown and associated mood changes may have differential effects on individuals' alcohol consumption [15,21,[35][36][37]. The association between increased drinking behaviour and poorer mood and depression during the pandemic has also been observed in Australia [26,33], the UK [15], Belgium [22], Greece [27], and the USA [14,23,35].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, a reduction in alcohol consumption was shown to be an adequate coping mechanism for lockdown related mood and stress effects, for maintaining adequate immune fitness, and to reduce their susceptibility of experiencing COVID-19-related symptoms. Our findings, summarized in Figure 7, are in line with previous publications outlined in the introduction, showing that the COVID-19 lockdown and associated mood changes may have differential effects on individuals' alcohol consumption [15,21,[35][36][37]. The association between increased drinking behaviour and poorer mood and depression during the pandemic has also been observed in Australia [26,33], the UK [15], Belgium [22], Greece [27], and the USA [14,23,35].…”
Section: Discussionsupporting
confidence: 90%
“…In our first analysis of the alcohol consumption data of the Dutch 'Corona Lockdown: how fit are you?' (CLOFIT) study we found no overall effect on alcohol consumption when comparing lockdown versus pre-lockdown weekly alcohol consumption [36,37]. However, in this study, the sample analysed for alcohol consumption was not a homogenous group, and included both participants that increased or decreased alcohol consumption.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…A subsample of alcohol consumers from an online survey was used for the current analysis ( Kiani et al. , 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The current analysis includes data collected from the “Corona Lockdown: how fit are you?” (CLOFIT) study [ 33 ]. An online survey was conducted between 24th of June and the 26th of July 2020 to investigate the psychosocial and health consequences of the COVID-19 pandemic in The Netherlands.…”
Section: Methodsmentioning
confidence: 99%